2015
DOI: 10.1371/journal.pone.0138614
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanocomposite Scaffold-Induced Stimulation of Migration and Odontogenesis of Human Dental Pulp Cells through Integrin Signaling Pathways

Abstract: Magnetism is an intriguing physical cue that can alter the behaviors of a broad range of cells. Nanocomposite scaffolds that exhibit magnetic properties are thus considered useful 3D matrix for culture of cells and their fate control in repair and regeneration processes. Here we produced magnetic nanocomposite scaffolds made of magnetite nanoparticles (MNPs) and polycaprolactone (PCL), and the effects of the scaffolds on the adhesion, growth, migration and odontogenic differentiation of human dental pulp cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 41 publications
(42 reference statements)
1
27
0
Order By: Relevance
“…ALP activity, the mRNA expression of specific markers (e.g., osteocalcin and osteopontin) and alizarin red staining on nanocomposite scaffolds consisting of PCL and magnetite nanoparticles showed how magnetic features can stimulate the differentiation process [60]. The potential to upregulate specific integrin subunits and to activate downstream pathways (e.g., focal adhesion kinase-FAK, paxillin, p38, and ERK/MAPK) was reported [60].…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity, the mRNA expression of specific markers (e.g., osteocalcin and osteopontin) and alizarin red staining on nanocomposite scaffolds consisting of PCL and magnetite nanoparticles showed how magnetic features can stimulate the differentiation process [60]. The potential to upregulate specific integrin subunits and to activate downstream pathways (e.g., focal adhesion kinase-FAK, paxillin, p38, and ERK/MAPK) was reported [60].…”
Section: Discussionmentioning
confidence: 99%
“…Yun et al . () cultured human dental pulp cells on a magnetic nanocomposite scaffold and found that the scaffold enhanced the migration and dentinogenesis of cells via the phosphorylation of the p38 and ERK MAPK signalling pathways. Kwon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Collagen or PCL-gelatin-based nanofibrous scaffolds incorporating bioactive glass nanoparticles were developed for dentin-pulp regeneration and showed enhanced growth and odontogenic differentiation from human DPSCs compared to collagen nanofibrous scaffold via integrin-mediated process [5,49]. Magnetite nanoparticles were incorporated to PCL due to its intriguing physical cues that can tailor the behaviors of DPSCs [50]. The effects of these nanocomposite nanofibers on the adhesion, growth, migration, and odontogenic differentiation of human DPSCs were significantly remarkable compared to those of polymeric nanofibers.…”
Section: Pulp-dentin Complex Regenerationmentioning
confidence: 99%